2010
DOI: 10.1017/s0029665110003228
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and food-related quality of life in free-living older adults

Abstract: Malnutrition in older people is related to increased mortality, risk of fracture, infections and specific nutrient deficiencies, leading to a variety of health-related conditions that can greatly affect the quality of life (1) . Although institutionalised older adults have been shown to be at high risk of malnutrition (2) , previous research has shown that, even among independent older people, 3 % of men and 6 % of women are underweight (3) . With the proportion of the UK population that is over 75 years of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…This has identified that in this study, a large number of older patients (76%) were at the risk of malnutrition or are already malnourished; however, the sample is small. This data will be used to further understand the pathogenesis of malnutrition by comparison with that already collected and presented ( 5 ) from free-living older adults and those in care homes.…”
mentioning
confidence: 99%
“…This has identified that in this study, a large number of older patients (76%) were at the risk of malnutrition or are already malnourished; however, the sample is small. This data will be used to further understand the pathogenesis of malnutrition by comparison with that already collected and presented ( 5 ) from free-living older adults and those in care homes.…”
mentioning
confidence: 99%